Antinociceptive and anti-inflammatory effects of the citrus flavanone naringenin - Chung, Ting-Wen (Tzu Chi Med J, 2019)
OBJECTIVE: Naringenin, a flavonoid found in citrus fruits, has notably diverse pharmacological properties. In the present study, we investigated the antinociceptive and anti-inflammatory effects of naringenin. MATERIALS AND METHODS: The antinociceptive effects were evaluated using hot-plate, acetic acid-induced writhing, and tail-flick assays in mice and rats. The anti-inflammatory effects were examined by a carrageenan-induced paw edema test in rats. RESULTS: Naringenin (100 or 200 mg/kg, oral administration) significantly delayed the reaction time of mice to thermal stimulation generated by a hot plate and a tail-flick unit and reduced the acetic acid-induced writhing response in mice. In addition, naringenin significantly decreased paw edema induced by carrageenan in rats, showing its anti-inflammatory effect. CONCLUSION: Our results show that naringenin has therapeutic potential with antinociceptive and anti-inflammatory properties and can further be exploited for the development of drugs for pain and inflammatory-related diseases.